1993
DOI: 10.1177/002246699302600407
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Developmental Outcomes in Young Children with Disabilities in Integrated and Segregated Settings

Abstract: This article reviews the literature comparing outcomes for young children with disabilities in integrated and segregated settings. An examination of research methodology, dependent measures, and programmatic variables is used to analyze the effects of preschool integration across 22 studies. Despite some methodological weaknesses, an analysis of findings provides support for the benefits of preschool integration with respect to social and other behavioral outcomes. Children's developmental outcomes over time h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(112 citation statements)
references
References 32 publications
(84 reference statements)
5
104
0
3
Order By: Relevance
“…These diverse examinations and the numerous methodological issues in the studies as identified by the reviewers (Gottlieb, 1981;Gresham & MacMillan, 1997) We note Leinhardt and Pallay's (1982) (Buysse & Bailey, 1993;Slavin, 1984).…”
Section: The Most Appropriate Environment For the Edu-mentioning
confidence: 99%
“…These diverse examinations and the numerous methodological issues in the studies as identified by the reviewers (Gottlieb, 1981;Gresham & MacMillan, 1997) We note Leinhardt and Pallay's (1982) (Buysse & Bailey, 1993;Slavin, 1984).…”
Section: The Most Appropriate Environment For the Edu-mentioning
confidence: 99%
“…Both unilateral and reciprocal friendships occur at the same rate in inclusive or segregated settings (Guralnick et al ., 1996a) . In addition, although the proportion of negative interactions is increased slightly in inclusive settings, the social interaction levels of children with delays have consistently been found to be higher in inclusive as opposed to segregated settings (Buysse & Bailey, 1993 ;Guralnick et al ., 1996a ;Guralnick & Groom, 1988b).…”
Section: Psychological Meaning Of Social Separationmentioning
confidence: 99%
“…As educating students with developmental disabilities in inclusive settings is now considered the preferred educational option in many school communities (Coots, Bishop, Grenot-Scheyer, & Falvey, 1995;Falvey, 1995;Westling & Fox, 2004), the investigation of relationships in inclusive settings is imperative. Although quite a few studies have focused on comparisons between relationships of children in inclusive as opposed to specialised settings (Buysse & Bailey, 1993;Buysse et al, 2002;Freeman, 2000;Heiman, 2000), few studies have investigated the relationships of children who have all been exposed to inclusive settings for several years. In addition, the majority of research has focused on middle class and Caucasian populations and has primarily been conducted in cities in North America or Great Britain.…”
mentioning
confidence: 99%